Boozy Nights and Violent Fights: Perceptions of Environmental Cues to Violence and Crime in Licensed Venues. Issue 9 (May 2019) - de Andrade, Dominique; Homel, Ross; Mazerolle, Lorraine
This article examines perceptions of environmental cues to crime, violence, and injuries in barroom settings, and how they differ between bar fight participants and non-participants. Bouncer friendliness, patron sex composition, and room temperature were chosen as experimental variables based on three criteria: (a) emerged as a theme in bar user focus groups, (b) unclear effects in the literature, and (c) policy relevant and easy to modify. These experimental variables were manipulated in written vignettes set in a bar. A three-part online questionnaire recorded 681 male university students' responses to questions on demographics, the experiment, drinking and clubbing habits, and the Snell Masculinity Scale. A 2 × 2 × 2 randomized independent groups factorial design with covariates was embedded in the questionnaire, measuring the effects of the experimental variables on bar users' perceived fear of victimization, likelihood and frequency of crime, venue preference, and perceived severity of injuries after accounting for prior bar fight participation and masculinity. Participants generally rated perceived fear of victimization, likelihood and frequency of crime, and severity of injuries to be highest when the bouncer was unfriendly, the temperature was hot, and patrons were majority male. Only main effects were significant ( p < .01). Masculinity scale responses were not related to participant perceptions. While fight participants (9.8% of the sample) and non-participants had similar perceptions of the risk associated with certain environmental cues, fight participants were significantly (a) less fearful of victimization in settings they perceived as dangerous and (b) more willing to drink in any hypothetical venue.